Characterization of twenty-two fig cultivars (Ficus carica L.) collected in north-eastern Algeria - Belattar, Hakima (International Journal of Sciences and Natural Ressources, 2022)
There is a significant lack of information and research about Algerian figs, whether for varietal characterization, preservation or enhancement of this genetic resource. The fig tree (Ficus carica L.) is one of the oldest cultivated fruits in the world. Algeria is among the first Mediterranean countries producing figs. The evaluation of the ITAFV collection will allow the establishment of a database for the identification of ecotypes of interest for the direct development of the species and its future use in variety breeding programs. Morphological characterization and pomological evaluation were studied on the basis of the methodology established by IPGRI and CIHEAM, 2003 during three seasons (2012, 2013 and 2014). The phenotypic variability of the twenty-two cultivars shows the richness of the fig heritage of the ITAFV collection, Skikda (Algeria). The hierarchical classification based on the morphological descriptors of the leaf and the fruit has clearly revealed the importance of these parameters in the discrimination of fig varieties. The morpho-pomological characters used for the leaves and fruits indicated a fairly significant genetic variability between the cultivars studied with a relatively high degree of polymorphism.